Challenges and opportunities for involving patients and the public in acute antimicrobial medicine development research: an interview study - Gibson, Andy (BMJ Open, 2019)
OBJECTIVES: To explore what approaches to patient and public involvement (PPI) in antimicrobial medicines development are currently being used, what the impacts of PPI are on antimicrobial medicines development and what the barriers are to its implementation. DESIGN: Interview study. SETTING: Antimicrobial medicines development research. PARTICIPANTS: Principal investigators known to have led studies involving PPI or expressed an interest in PPI. RESULTS: There is very little published work on PPI in antimicrobial research. Individual interviewees expressed scepticism about the contribution that PPI could make to different stages of the medicines development life cycle but collectively identified a range of potential benefits of PPI covering most stages of the medicines development process. CONCLUSIONS: A major issue in developing PPI in antimicrobial medicines development research will be in overcoming the view that, at best, PPI has only a marginal contribution to make in this area of research. The findings from this study, although mixed, suggest that well-designed PPI has an untapped potential to enhance antimicrobial research.